'In and Out of Each Other's Worlds': The Art of Mother and Daughter, Helga Michie and Ruth Rix. Issue 1 (1st March 2023) - Dickson, Rachel
Abstract: The art of Austrian Kindertransportee Helga Michie has been much discussed, particularly in the context of the work of her identical twin, Holocaust writer Ilse Aichinger. This article, however, focuses in particular on Michie's daughter, English-born painter Ruth Rix, and the relationship with her mother. It considers Rix's appropriation of images inspired by Austrian family photographs and more than a hundred picture postcards, provided by Michie. Across two generations, the art of mother and daughter – overshadowed by the Holocaust – is introduced, examining how each influenced the other, with Rix grappling with both memory and postmemory. As she suggests, Michie offered a 'doorway' into Austria, and she, conversely, one to Englishness, though both strayed constantly 'in and out of each other's worlds'. Motifs inspired by private and wider tragedies highlight shared concerns: fracture, family, memory, identity, loss and notions of home, creating a trans-generational body of work which, when taken as a whole, is even more powerful than when viewed apart.